Subaponeurotic ligation of the communicating leg veins in the treatment of chronic venous insufficiency of the lower limbs: Indications and results - Delgado, Bolivar; Gateño, Nisso; Perrier, José P. (Cirugía del Uruguay, 1979)
The authors analyze indications and results of subaponeurotic ligation of venae perforantis of leg far the treatment of chronic venous insufficiency of lower limbs, on the basis of a case material consisting of 100 such operation. The main indication (85 %) was the association of insufficiency of veinae perforantis and superficial and/ or deep venous insufficiency with distal trophic disorders. The remaining group consisted of postphlebitic seque la ( 15 % ) which comprises 11 % of deep venous systems definitively obstructed. Long - term controls of 66 % of patients showed an overall 85 % good resul'ts; and these figures can be as high as 100 % when surgery is performed during the early stages of the disease. The authors lay considerable emphasis on this fact to show that this type of surgery should be performed as early as possible and should not merely be resorted to upon failure of isolated operations on superficial venous system.